Optimizing the shape of the prosthetic aortic leaflet valve - Konderla, Piotr; Patralski, Krzysztof (Computer Assisted Methods in Engineering and Science, 2006)
The object under study reported on in this paper was an aortic valve based on a natural aortic valve as the original. Simulations were carried out to examine the functioning of a valve which was loaded with varying pressure until a buckling of the leaflets and a full opening of the valve were observed. The aim of the study was the optimal choice of the geometric and mechanical parameters for the class of construction assumed for analysis.